2011
DOI: 10.1017/s0007114511006143
|View full text |Cite
|
Sign up to set email alerts
|

Teleost fish larvae adapt to dietary arachidonic acid supply through modulation of the expression of lipid metabolism and stress response genes

Abstract: Dietary fatty acid supply can affect stress response in fish during early development. Although knowledge on the mechanisms involved in fatty acid regulation of stress tolerance is scarce, it has often been hypothesised that eicosanoid profiles can influence cortisol production. Genomic cortisol actions are mediated by cytosolic receptors which may respond to cellular fatty acid signalling. An experiment was designed to test the effects of feeding gilthead sea-bream larvae with four microdiets, containing grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 65 publications
4
46
0
1
Order By: Relevance
“…Also in agreement with the present study, a range of larval and juvenile marine species such as Atlantic cod Gadus morhua , gilthead sea bream Sparus aurata (Alves Martins et al, 2012;Atalah et al, 2011a;Fountoulaki et al, 2003), Senegalese sole (Villalta et al, 2005) and turbot (Estévez et al, 1999), were able tolerate a wide range of dietary ARA levels with growth and survival found to be independent of ARA inclusion. In agreement, several recent studies have further demonstrated that balanced ARA and EPA are more critical than either individual FA in terms of growth and other metabolic processes further highlighting the need for understanding the optimal LC-PUFA balance (Norambuena et al, 2015;Norambuena et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Also in agreement with the present study, a range of larval and juvenile marine species such as Atlantic cod Gadus morhua , gilthead sea bream Sparus aurata (Alves Martins et al, 2012;Atalah et al, 2011a;Fountoulaki et al, 2003), Senegalese sole (Villalta et al, 2005) and turbot (Estévez et al, 1999), were able tolerate a wide range of dietary ARA levels with growth and survival found to be independent of ARA inclusion. In agreement, several recent studies have further demonstrated that balanced ARA and EPA are more critical than either individual FA in terms of growth and other metabolic processes further highlighting the need for understanding the optimal LC-PUFA balance (Norambuena et al, 2015;Norambuena et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown the role of ARA mediation on the eicosanoid cascade with the concomitant regulation of overall fish physiology including maturation, endocrinology and health stress response. Accordingly, dietary ARA supplementation has increasingly received consideration for possible functional feed formulation (Alves Martins et al, 2012;Norambuena et al, 2013c;Tian et al, 2014;Van Anholt et al, 2004;Xu et al, 2010). However, and to the best of authors' knowledge, it is surprising to note that this study is the first to assess the effects of dietary ARA on performance and fatty acid composition in juvenile Atlantic salmon.…”
Section: Discussionmentioning
confidence: 97%
“…In fish, ARA is mainly stored in polar lipids and is a minor component of fish cell membranes compared to DHA and EPA (Fountoulaki et al, 2003;Tocher, 2010). Recent research has focused on evaluating the importance of ARA in fish nutrition, with gradual elucidation of the physiological functions of the bioactive eicosanoids, fish performance and fatty acid digestibility (Alves Martins et al, 2012;Martinez-Rubio et al, 2013;Norambuena et al, 2012a;Norambuena et al, 2014;Trullàs et al, 2015). A growthpromoting activity of dietary ARA in different fish species, particularly during juvenile stages, has been reported.…”
mentioning
confidence: 99%
“…Thus, in light of the recently increased interest in the roles of dietary ARA, as an important and somewhat overlooked LC-PUFA (Alves Martins et al, 2012;Bell and Sargent, 2003;Norambuena et al, 2013a), this study can be considered instrumental also for providing evidence that any inclusion of, or even fortification with ARA, should not cause concern about possible negative effects on nutrients and fatty acids digestibility.…”
Section: Tablementioning
confidence: 99%